Hormonal and physiological changes driven by fungal endophytes increase Antarctic plant performance under UV-B radiation. (August 2018) - Ramos, Patricio; Rivas, Natali; Pollmann, Stephan; Casati, Paula; Molina-Montenegro, Marco A.
Abstract: Antarctic environments are amongst the most stressful habitats for life on Earth, with high intensities of solar UV-B radiation reaching the land surface. In this study, we evaluated how the photochemical efficiency, cell damage and reproductive biomass of Antarctic pearlwort ( Colobanthus quitensis ) were affected by different intensities of UV-B radiation in the absence and presence of fungal endophytes. In addition, we evaluated the hormonal content of plants at different UV-B radiation intensities and how hormonal content was affected by endophytes. Overall, plants exposed to UV-B radiation showed higher numbers of flowers, higher total biomass and lower lipid peroxidation in the presence of endophytes compared with plants without endophytes. Photochemical efficiency was unaffected. Fungal endophytes affected the content of salicylic acid, jasmonate, indole-3-acetate and abscisic acid in shoot tissue of plants exposed to UV-B radiation. These results suggest that endophytes could modulate the hormonal content of C. quitensis to improve its ecophysiological performance under high UV-B radiation.